Association analysis identifies 65 new breast cancer risk loci - Michailidou, Kyriaki; Arndt, Volker; Brenner, Hermann; Burwinkel, Barbara; Hamann, Ute; Kaaks, Rudolf; Kabisch, Maria; Schneeweiss, Andreas; Sohn, Christof; Chang-Claude, Jenny (Nature, 2017)
Association analysis identifies 65 new breast cancer risk loci, predicts target genes for known risk loci and demonstrates a strong overlap with somatic driver genes in breast tumours.
Gesehen am 22.11.2017